The Supercritical Pile Gamma-Ray Burst Model: The GRB Afterglow Steep Decline and Plateau Phase - Sultana, J.; Kazanas, D.; Mastichiadis, A. (2013)
We present a process that accounts for the steep decline and plateau phase of the Swift X-Ray Telescope (XRT) light curves, vexing features of gamma-ray burst (GRB) phenomenology. This process is an integral part of the "supercritical pile" GRB model, proposed a few years ago to account for the conversion of the GRB kinetic energy into radiation with a spectral peak at E pk ~ mec 2. We compute the evolution of the relativistic blast wave (RBW) Lorentz factor Γ to show that the radiation-reaction force due to the GRB emission can produce an abrupt, small (~25%) decrease in Γ at a radius that is smaller (depending on conditions) than the deceleration radius RD . Because of this reduction, the kinematic criticality criterion of the "supercritical pile" is no longer fulfilled. Transfer of the proton energy into electrons ceases and the GRB enters abruptly the afterglow phase at a luminosity smaller by ~mp /me than that of the prompt emission. If the radius at which this slow-down occurs is significantly smaller than RD , the RBW internal energy continues to drive the RBW expansion at a constant (new) Γ and its X-ray luminosity remains constant until RD is reached, at which point it resumes its more conventional decay, thereby completing the "unexpected" XRT light curve phase. If this transition occurs at R ~= RD , the steep decline is followed by a flux decrease instead of a "plateau," consistent with the conventional afterglow declines. Besides providing an account of these peculiarities, the model suggests that the afterglow phase may in fact begin before the RBW reaches R ~= RD , thus providing novel insights into GRB phenomenology.
Keywords: Astrophysics - High Energy Astrophysical Phenomena; cosmological parameters; gamma-ray burst: general